1992
DOI: 10.1063/1.1143783
|View full text |Cite
|
Sign up to set email alerts
|

Sagitally focusing scanning monochromator produces 0.4-mm focus (abstract)

Abstract: A sagitally focusing stage has been constructed for the double-crystal scanning monochromator on beam line X9-A at the NSLS which can be exchanged with the normally used flat crystal stage. The bending device located at 12.0 m from the source is designed to accept a beam up to 200-mm wide. The monochromator with bending stage can be scanned over Bragg angles from 10° to 71° corresponding to photon energies from 11.4 to 2.1 keV with Si-111 crystals. In conjunction with the vertically focusing mirror a point foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The bender is mounted on a double stage with the capability to move vertically and laterally along the beam in order to preserve a fixed exit beam when the energy of the monochromator is changed. The design principles of a sagittal bender with a four-point loading geometry are described in detail by Howell & Hastings (1983), Rosenbaum et al (1992) and Ice & Sparks (1994). The sagittal (horizontal) focusing is essential for a bending-magnet beamline to collect a signifi-cant portion of the horizontal beam.…”
Section: Componentmentioning
confidence: 99%
“…The bender is mounted on a double stage with the capability to move vertically and laterally along the beam in order to preserve a fixed exit beam when the energy of the monochromator is changed. The design principles of a sagittal bender with a four-point loading geometry are described in detail by Howell & Hastings (1983), Rosenbaum et al (1992) and Ice & Sparks (1994). The sagittal (horizontal) focusing is essential for a bending-magnet beamline to collect a signifi-cant portion of the horizontal beam.…”
Section: Componentmentioning
confidence: 99%
“…We have chosen to sagittally bend the second monochromator crystal as the means to focus the beam in the horizontal direction. Prior experience (Rosenbaum et al, 1992) has shown that a sagittally focusing crystal monochromator produces a very clean aberration-free focus. The disadvantage of the focal length changing with a change of the monochromator Bragg angle, i.e.…”
Section: Optical Layoutmentioning
confidence: 99%